Developing Story Card Media to Cultivate Environmental Love in Early Childhood in Kindergarten - Winda Arie Andriyani; Azi Matur Rahmi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Instilling a love for the environment from an early age is an important part of character building for children, but its implementation in early childhood education institutions still requires the support of interesting learning media, in accordance with the characteristics of child development, and able to connect environmental messages with meaningful learning experiences. This condition encourages the need to develop media that can facilitate interactive learning so that children can more easily understand and apply environmentally conscious behavior in everyday life. This study aims to develop story card media as a means to foster a love for the environment in early childhood in kindergartens in Cibitung District. The study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects were children aged 5–6 years at Rainbow Kids Kindergarten and Husnul Khotimah Kindergarten. The results of expert validation showed a feasibility level of 98.6% for the material aspect and 85.3% for the media aspect, both of which are categorized as very valid. The practicality test by teachers obtained a score of 90% with a very practical category. The effectiveness test results showed an increase in environmental awareness, from 71% in the pre-test to 93% in the post-test. These findings demonstrate that story cards are valid, practical, and effective in fostering environmental awareness in children aged 5–6 years. This medium can also be an alternative for early childhood education teachers in integrating environmental awareness character education through engaging, contextual, and developmentally appropriate learning activities